THE ROLE OF WORK MOTIVATION IN INFLUENCE ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Nasution, Donny Alnis; Hasan, Muh; Efendi, Reni Amelia (Univesitas Muhammadiyah Tangerang, 2024)
The purpose of this research is to determine the role of work motivation in influencing organizational citizenship behavior (OCB) with job satisfaction as an intervening variable in PT employees. Torabika Eka Semesta. This research uses an associative method with a quantitative approach. The sample was 103 people using questionnaire techniques. Descriptive statistical analysis and data evaluation with SEM-PLS for hypothesis testing. Data processing was assisted by Microsoft Excel and Warp PLS 7.0 software. Based on the test, the contribution of work motivation (X) to job satisfaction (Z) is 19.9%, while work motivation (X) and job satisfaction (Z) to Organizational Citizenship Behavior (OCB) (Y) is 30.6%. The effect size results of the influence of Work Motivation (X) on Organizational Citizenship Behavior (OCB) (Y) is 0.070 which is classified as weak, Work Motivation (X) on Job Satisfaction (Z) is 0.199 which is classified as medium, Job Satisfaction (Z) on Organizational Citizenship Behavior ( OCB) (Y) of 0.235 is classified as medium. The results of the analysis show that Work Motivation (X) has a positive and significant effect on Organizational Citizenship Behavior (OCB) (Y). Work Motivation (X) has a positive and significant effect on Job Satisfaction (Z). Work Motivation (X) has a positive and significant effect on Organizational Citizenship Behavior (OCB) (Y) through Job Satisfaction (Z). Job Satisfaction (Z) has a positive and significant effect on Organizational Citizenship Behavior (OCB) (Y). Therefore, Job Satisfaction can mediate the Effect of Work Motivation on Organizational Citizenship Behavior (OCB). The VAF calculation results show a value of 52.9412%, which is between 20%-80%, so job satisfaction is categorized as partial mediation.